2017
DOI: 10.1186/s13072-017-0134-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imprinting does not reduce the dosage of UBE3A in neurons

Abstract: BackgroundThe ubiquitin protein E3A ligase gene (UBE3A) gene is imprinted with maternal-specific expression in neurons and biallelically expressed in all other cell types. Both loss-of-function and gain-of-function mutations affecting the dosage of UBE3A are associated with several neurodevelopmental syndromes and psychological conditions, suggesting that UBE3A is dosage-sensitive in the brain. The observation that loss of imprinting increases the dosage of UBE3A in brain further suggests that inactivation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…For AS, mouse models have been used to implicate loss of UBE3A expression in the brain as the primary cause of specific deficits in AS 15 . However, few studies have been performed in human peripheral tissues 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For AS, mouse models have been used to implicate loss of UBE3A expression in the brain as the primary cause of specific deficits in AS 15 . However, few studies have been performed in human peripheral tissues 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have been performed in human peripheral tissues 16 , 17 . UBE3A is a key gene in neurodevelopment and is thought to be imprinted only in neurons, where it is expressed from the maternal allele in humans and mice 15 . Interestingly in other cell types UBE3A has bi-allelic expression 18 and is thought to be consistently expressed from both alleles in different peripheral tissues 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we could not observe paternal UBE3A silencing in neurotypical hCOs ( Figure 3B). This is expected as previous reports in mice showed that maternal UBE3A dosage compensates for paternal imprinting (Hillman et al, 2017). Therefore, to observe paternal UBE3A silencing we obtained a human induced pluripotent stem cell line previously generated from an Angelman syndrome patient (Chamberlain et al, 2010) and created hCOs from them (AS hCO).…”
Section: Hcos Reveal Distinct Patterns Of Ube3a Expression In Progenimentioning
confidence: 62%
“…Epilepsy is a common co-morbidity with ASD in general (15,(38)(39)(40)(41)(42)(43), but can be even more severe and difficult to treat in syndromic forms of ASD like Dup15q syndrome (1,16,44,45). In fact, most children with isodicentric duplications of 15q that include four copies of the UBE3A gene, presumably active in glia where it is not imprinted (18)(19)(20)(21), suffer from pharmacoresistant seizures (16). Here we utilized our fly model of Dup15q to screen for previously approved compounds that can suppress seizures due to elevated levels of UBE3A in glia, not neurons (17).…”
Section: A Role For Serotonin Signaling In Dup15q Seizure Suppressionmentioning
confidence: 99%